Warfare in Eastern Europe, 1500-1800
1 online resource (vi, 364 pages)
Keywords: This volume examines continuities and new developments in the conduct of warfare in early modern Eastern Europe from the early sixteenth century, when Ottoman imperial expansion reached the Danube and Crimea, to the late eighteenth century, when the Polish-Lithuanian Commonwealth was partitioned out of existence and Russia rolled back Ottoman power from Ukraine and Moldavia. Contributors include specialists in Russian, Polish, Ottoman, Habsburg, Cossack, and Crimean Tatar history. The essays engage military history understood in the broadest sense and treat such subjects as taxation, recruitment, the sociology and culture of officer corps, logistics, command-and-control, and ideology as well as technology and tactics. The volume aims at facilitating comparative study of Eastern European military development across Eastern Europe and its points of divergence from military practice in the West. Contributors are Virginia H. Aksan, Brian J. Boeck, Peter B. Brown, Brian Davies, Dariusz Kupisz, Erik Lund, Janet Martin, Oleg Nozdrin, Victor Ostapchuk, Geza Palffy and Carol Belkin Stevens.